Cognitive Mechanisms of False Facial Recognition - Edmonds, Emily Charlotte (The University of Arizona., 2011)
Face recognition involves a number of complex cognitive processes, including memory, executive functioning, and perception. A breakdown of one or more of these processes may result in false facial recognition, a memory distortion in which one mistakenly believes that novel faces are familiar. This study examined the cognitive mechanisms underlying false facial recognition in healthy older and younger adults, patients with frontotemporal dementia, and individuals with congenital prosopagnosia. Participants completed face recognition memory tests that included several different types of lures, as well as tests of face perception. Older adults demonstrated a familiarity-based response strategy, reflecting a deficit in source monitoring and impaired recollection of context, as they could not reliably discriminate between study faces and highly familiar lures. In patients with frontotemporal dementia, temporal lobe atrophy alone was associated with a reduction of true facial recognition, while concurrent frontal lobe damage was associated with increased false recognition, a liberal response bias, and an overreliance on "gist" memory when making recognition decisions. Individuals with congenital prosopagnosia demonstrated deficits in configural processing of faces and a reliance on feature-based processing, leading to false recognition of lures that had features in common from study to test. These findings may have important implications for the development of training programs that could serve to help individuals improve their ability to accurately recognize faces.